Zum Gedenken an Erwin Panofsky (1892-1968)/Reden aus Anlass der Benennung des Hörsaals C im Hauptgebäude der Universität Hamburg in Erwin-Panofsky-Hörsaal am 20. Juni 2000 - Krause, Eckart; Nicolaysen, Rainer (Hamburger Universitätsreden Neue Folge, 2010)
Since the 80th anniversary of the University of Hamburg in 1999, an important form of historical remembrance has been the naming of the restored lecture halls in the main university building, the "ESA 1", after the victims of racism, intolerance and inhumanity in the "Third Reich".The two largest, halls A and B,which were given the names of the philosopher Ernst Cassirer and the German scholar Agathe Lasch in 1999, were followed the following year by C (Erwin Panofsky), M (Emil Artin) in April 2005 and J (Magdalene Schoch) in June 2006. The speeches given on this occasion, which can be read in the "Neue Folge" of the "Hamburger Universitätsreden" (Hamburg University Speeches) provide information on the events for the respective naming of the events, especially on their reasons for naming them, with the exception of the speeches given at the time when Lecture Hall C was named. The speeches were extensively annotated by the editors and supplemented with a detailed appendix.